KEBIJAKAN NEGARA TERHADAP PRT MIGRAN DI INDONESIA: TELAAH GENDER DAN HUBUNGAN INTERNASIONAL - Ani Soetjiptio (LIPI Press, 2017)
Studies on migrant domestic workers have been widely discussed through various social, politic as well as economic analyses. In international relations, the studies on migrant domestic workers can be analyzed through a number of perspectives. In addition to international political economic perspective, studies on migrant domestic workers also frequently use the international migration theory. This paper discusses and highlights the issue of migrant domestic workers overseas through gender and feminism perspectives as well as their intersection with international political economic and international migration perspectives. Gender and feminism perspectives perceive individual and personal experience to be strongly correlated with the global situation and international structure. Using this analysis, one can explain why women from third world countries such as Indonesia, Philippines, and Bangladesh have gone into global workforce markets, which mostly are segmented into low-paid, lack of protection employment, and informal sectors (domestic workers). They frequently have to face isolation, exploitation, and multi-layered discrimination. This paper aims to map the issues of Indonesian women migrant workers in more thorough manner as well as reviewing state’s policy on migrant workers in the current Jokowi-JK administration. This article consists of three parts. First is the current empirical phenomenon of Indonesian migrant domestic workers along with various issues they are engulfed in. The second part is conceptual framework, i.e. feminist lens and its intresection with international political economy as well as international migration in addressing migrant domestic workers issues and how the issue is advocated. The last part highlights the use of such a framework to discuss about migrant domestic worker issues in Indonesian context. Kajian tentang tentang PRT Pekerja migran sudah banyak dibahas lewat beragam analisis sosial, politik maupun ekonomi. Dalam ilmu hubungan internasional, kajian tentang Pekerja Rumah Tangga (PRT) migran bisa dianalisis lewat beragam perspektif. Selain lewat perspektif ekonomi politik internasional, kajian tentang PRT migran juga biasa dibahas lewat teori migrasi internasional. Tulisan ini akan membahas dan mengkaji masalah PRT migran di luar negeri lewat perspektif gender dan feminisme persilangannya dengan lensa ekonomi politik internasional dan migrasi internasional. Perspektif gender dan feminisme melihat bahwa pengalaman personal perseorangan sangat terkait erat satu sama lain dengan situasi global dan struktur internasional. Melalui pisau analisis tersebut dijelaskan mengapa perempuan dari dunia ketiga, seperti Indonesia, Filipina, Bangladesh terlempar ke pasar kerja global, dan tersegmentasi sebagian besar dalam lapangan kerja yang berupah rendah, minim perlindungan, sebagian besar berada dalam sektor informal sebagai PRT, yang cirinya sering terisolasi, serta tidak jarang mengalami eksploitasi dan diskriminasi berlapis lapis. Lewat tulisan ini diharapkan peta persoalan buruh migran perempuan Indonesia tidak hanya bisa dipahami dengan lebih jeli, tetapi juga kebijakan negara terhadap PRT Migran di era pemerintahan Jokowi- JK saat ini bisa ditelaah. Tulisan ini akan terdiri dari tiga bagian. Bagian pertama adalah fenomena empirik situasi PRT migran Indonesia dengan berbagai persoalannya. Bagian kedua memaparkan kerangka pemikiran melalui lensa feminisme dan persilangannya dengan ekonomi politik internasional serta migrasi internasional dalam menyikapi persoalan PRT dan bagaimana isu tersebut diadvokasikan. Bagian terakhir dengan menggunakan kerangka pemikiran tersebut dibahas persoalan PRT migran dalam konteks Indonesia